Community service as an alternative punishment: the extent of its applications on the categories of crimes and offender in Malaysia - Abdul Rahim, Anita; Tg Zainudin, Tg Noor Azira; Samuri, Mohd al Adib; Abdul Rahim, Adibah (Contemporary Research Center Australia, 2013)
The order of community service is a fairly new concept in the criminal justice system in Malaysia. This order is a non-custodial punishment which acts as an alternative to the custodial punishment. Even though there are several existing legal provisions pertaining to community service in Malaysia, their application is still ambiguous particularly regarding the categories of crime and offenders involved. Hence there are two issues that need to be addressed; firstly, how will the community service order be imposed, and secondly on which categories of crimes and offenders will it be imposed? This article seeks to address these two issues by discussing community service order as an alternative or additional punishment, and the suitability of its application to specific categories of crimes and offenders.